FAKTOR-FAKTOR YANG MEMILIKI PENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI - Putri, Hertarisa; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to analyze the effect of solvency, liquidity, institutional ownership, managerial ownership and investment decisions on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2020. This company uses 88 manufacturing companies as samples with purposive sampling technique. Data processing was carried out using the Eviews 12 program. The results of this study indicate that solvency has a significant positive effect on firm value and managerial ownership has a significant negative effect on firm value. while liquidity, institutional ownership, and investment decisions have no significant positive effect on firm value. Hypothesis testing is done by using a panel data regression model.